(untitled) (Texas Journal of Medical Science, 2025)
Esophageal cancer remains one of the most aggressive forms of gastrointestinal malignancy, characterized by a high mortality rate and poor prognosis. Surgery, often combined with chemoradiation, remains the primary definitive treatment option. In recent years, considerable attention has been paid to the analysis of long-term outcomes, including overall and disease-free survival, quality of life, and the incidence of complications and tumor recurrence. This paper presents summarized clinical observational da ta characterizing the long-term effectiveness of surgical treatment. Key factors influencing survival are identified, including tumor morphology, degree of invasion, surgical radicality, resection margin status, and comorbidities. A comparative analysis of the outcomes of open and minimally invasive procedures is also conducted. The data obtained confirm the need for a comprehensive approach, multidisciplinary monitoring, and optimized postoperative patient care to improve five-year survival.